Women of childbearing age perspective on obesity: A qualitative study - Ika Nur Saputri; Delmi Sulastri; Mudjiran Mudjiran; Eva Chundrayetti; Nur Indrawaty Lipoeto; Defrin Defrin; Meri Neherta; Hafni Bachtiar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Obesity is an excessive increase in body fat that can cause health problems. It is characterized by a disturbance in the body's energy balance, namely a positive energy balance that is eventually stored in the form of fat in body tissues. Many factors influence obesity, especially in women of childbearing age. Purpose: To explore more deeply the perspectives of women of childbearing age with obesity in Deli Serdang Regency. Method: The study was qualitative descriptive conducted from September to December 2023 and within the scope of Deli Serdang Regency which has a prevalence of obesity in women of childbearing age of 32%. Six women of childbearing age were involved in this study using purposive sampling. Data were collected using in-depth interviews and analyzed using content analysis. Results: The study emerged themes: 1) educational, 2) hereditary factors, 3) knowledge, 4) attitude, 5) food intake, 6) physical activity, dan 7) sleep quality. Conclusion: The results found are factors that must be considered regarding obesity in women of childbearing age. We need to conduct quantitative research to see the extent of the relationship between the factors found and the incidence of obesity, to increase the independence of women of childbearing age in losing weight through controlling obesity in women of childbearing age.